Successful Efforts to Increase Diversity in a Cardiology Fellowship Training Program - Auseon, Alex J. (The Accreditation Council for Graduate Medical Education, 2013)
BACKGROUND: A large volume of literature has documented racial disparities in the delivery of cardiovascular care in the United States and that decreased access to procedures and undertreatment lead to worse outcomes. A lack of diversity among physicians is considered to be a major contributor. The fellowship training program in cardiovascular medicine at The Ohio State University Medical Center had never trained a fellow from a minority group underrepresented in medicine (URM) before 2007. INTERVENTION: In 2005, the fellowship made it a priority to recruit and match URM candidates in an effort to address the community's lack of diversity and disparities in cardiovascular care. METHODS: Program leaders revised the recruitment process, making diversity a high priority. Faculty met with members of diverse residency programs during visits to other institutions, the focus of interview day was changed to highlight mentorship, additional targeted postinterview communications reached out to highly competitive applicants, and a regular mentoring program was constructed to allow meaningful interaction with URM faculty and fellows. RESULTS: Since these changes were implemented, the program has successfully matched a URM fellow for 5 consecutive years. Such candidates currently make up 4 of 16 total trainees (25%) in the fellowship in cardiovascular medicine. CONCLUSIONS: The cardiovascular medicine fellowship training program at The Ohio State University was able to revise recruitment to attract competitive URM applicants as part of a concerted effort. Other educational programs facing similar challenges may be able to learn from the university's experiences.